Literature Review : Faktor-Faktor Penyebab Ketidaklengkapan Pengisian Formulir Informed Consent di Rumah Sakit - Nina Rahmadiliyani; Ni Wayan Kurnia Widya Wati (HB PRESS, 2022)
Informed consent is the approval of a medical action given by the patient or his closest family after receiving a complete explanation of the medical action to be carried out on the patient. The purpose of this study was to determine the factors causing the incomplete filling of the informed consent form at the hospital. The research method uses a literature study. The results showed that the incomplete informed consent filling in the hospital on the components of identification, important reporting, authentication and correct documentation, the factors causing incomplete filling of the informed consent form at the hospital due to lack of human resources due to limited workforce and lack of accuracy of installation officers. medical records so that the quality of the information produced is low and the implementation strategy of filling out a complete informed consent form in the hospital must have policies and SOPs, basically standard operating procedures.